2018
DOI: 10.3390/buildings8120168
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Daytime Radiative Cooling: Is It the Air Conditioner of the Future?

Abstract: Radiative cooling is a well-researched area. For many years, surfaces relying on radiative cooling failed to exhibit a sub-ambient surface temperature under the sun because of the limited reflectance in the solar spectrum and the reduced absorptivity in the atmospheric window. The recent impressive developments in photonic nanoscience permitted to produce photonic structures exhibiting surface temperatures much below the ambient temperature. This paper aims to present and analyze the main recent achievements c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(58 citation statements)
references
References 90 publications
0
58
0
Order By: Relevance
“…Against this backdrop, scientific breakthroughs in the field of materials sciences are expected to pave the way to new mitigation technologies. Among them, passive daytime radiative cooling ( Santamouris and Feng, 2018 ) and elastocaloric cooling ( Ulpiani et al, 2019 ) hold great promise.…”
Section: Discussionmentioning
confidence: 99%
“…Against this backdrop, scientific breakthroughs in the field of materials sciences are expected to pave the way to new mitigation technologies. Among them, passive daytime radiative cooling ( Santamouris and Feng, 2018 ) and elastocaloric cooling ( Ulpiani et al, 2019 ) hold great promise.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Recent studies have suggested that introducing light scattering particles/cavities into a polymer matrix can increase passive daytime radiative cooling by reflecting solar radiation. [26][27][28][29] Such materials should be designed to reflect the light in the wavelength (λ) range of ≈0.3-2.5 µm but allow thermal emission into the cold outer space through the atmospheric longwave infrared (LWIR) transmission window (λ ≈ 8-13 µm). Such an all-day radiation strategy is efficient in cooling (subambient cooling of 5-6 °C), without energy consuming and pollutant releasing.…”
Section: Doi: 101002/adma202000870mentioning
confidence: 99%
“…Polymer-based radiative cooling structures are likely to be the future devices due to their significant advantage in terms of ease of manufacturability and cost. 135 However, reliability and long-term stability are the main critical challenges that will always be there. Polymer degradation with time affects their long-term high solar reflectivity.…”
Section: Future Perspective and Challengesmentioning
confidence: 99%